A clinical study of the cutaneous manifestations of hyperthyroidism in Kashmir valley - India - Mohamad Abid Keen; Mohamad Hayat Bhat; Iffat Hassan; Parvaiz Ahmad Shah; Yasmeen Jabeen Bhat (Our Dermatology Online, 2016)
Introduction: Thyroid hormones are instrumental in regulating the health and appearance of skin and when the thyroid gland becomes underactive or overactive, a variety of skin problems result. These dermatologic manifestations may occur secondary to the abnormal thyroid hormone levels or due to the presence of thyroid autoantibodies that interact with skin components. Aims: The present study was designed to ascertain the varied cutaneous manifestations of hyperthyroidism. Methods: This was a hospital based cross sectional study conducted over a period of one year. A total of forty diagnosed cases of hyperthyroidism constituted the subject material for the study and were evaluated for the presence of any cutaneous manifestation. Results: In our study group of 40 patients, the predominant cutaneous symptom was increased sweating (80%), followed by heat intolerance (42.5%). The predominant cutaneous sign in hyperthyroid patients was increased skin temperature, noticed in 47.5% of patients. This was followed by soft, smooth and velvety skin (37.5%), palmar erythema (35%), fine thin hair (22.5%) and hyperpigmentation (10%). Conclusions: The interaction between thyroid gland and skin is very complex. So, dermatologists need to be cognizant of the ways in which these two organs interact.